Dynamics of singlet fission and electron injection in self-assembled acene monolayers on titanium dioxide. Issue 11 (26th February 2018) - Pace, Natalie A.; Arias, Dylan H.; Granger, Devin B.; Christensen, Steven; Anthony, John E.; Johnson, Justin C.
Abstract : Electron injection competes with singlet fission in disordered monolayers of tetracene and pentacene-based dyes on mesoporous TiO2 photoelectrodes. Abstract : We employ a combination of linear spectroscopy, electrochemistry, and transient absorption spectroscopy to characterize the interplay between electron transfer and singlet fission dynamics in polyacene-based dyes attached to nanostructured TiO2 . For triisopropyl silylethynyl (TIPS)-pentacene, we find that the singlet fission time constant increases to 6.5 ps on a nanostructured TiO2 surface relative to a thin film time constant of 150 fs, and that triplets do not dissociate after they are formed. In contrast, TIPS-tetracene singlets quickly dissociate in 2 ps at the molecule/TiO2 interface, and this dissociation outcompetes the relatively slow singlet fission process. The addition of an alumina layer slows down electron injection, allowing the formation of triplets from singlet fission in 40 ps. However, the triplets do not inject electrons, which is likely due to a lack of sufficient driving force for triplet dissociation. These results point to the critical balance required between efficient singlet fission and appropriate energetics for interfacial charge transfer.